Analisis Implementasi Sistem Online Single Submission (OSS) dalam Pelayanan Perizinan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Pekanbaru - Yona Armalita; Khotami (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
The purpose of this study is to examine the application of the OSS system in licensing services in DPMPTSP Pekanbaru City and identify existing obstacles. The research method used is qualitative descriptive with a case study approach. Data collection techniques include interviews, observations, and documentation of DPMPTSP officers and the public who use OSS services. Mazmanian and Sabatier's theory of policy implementation is used to analyze data that contains three main variables, namely problem characteristics, policy characteristics, and environmental factors. The results of the study show that the implementation of OSS in the Pekanbaru City DPMPTSP is not optimal. The main obstacles faced are the lack of public understanding of how to utilize the OSS system, technological disruption, and uneven socialization by relevant agencies. However, OSS has been proven to provide ease of electronic licensing if used appropriately. To ensure the long-term success of OSS implementation, human resource capacity development, infrastructure improvement, and strengthening public education are very important